Effect of Co-solution of Carbon Precursor and Activating Agent on the Textural Properties of Highly Porous Activated Carbon Obtained by Chemical Activation of Lignin With H3PO4 - Moulefera, Imane; García-Mateos, Francisco J.; Benyoucef, Abdelghani; Rosas, Juana M.; Rodríguez-Mirasol, José; Cordero, Tomás (Frontiers in Materials, 2020)
This work analyzes the effect of co-solution of carbon precursor and activating agent on the textural and surface chemistry properties of highly nanoporous activated carbons obtained by chemical activation of Alcell lignin with phosphoric acid. The success of this methodology highlights the possibility of directly using the liquors produced in organosolv process (Alcell) to prepare activated carbons by chemical activation with phosphoric acid. Co-solutions of lignin and phosphoric acid were submitted to a two steps thermal treatment, which consisted of a first oxidative treatment in air at 200 ºC, followed by a thermal treatment in N2 at 400 ºC, where activation of the oxidized lignin with phosphoric acid took place. A lignin-derived activated carbon with very high apparent surface area (2550 m2/g) and pore volume (1.30 cm3/g) was obtained with an initial phosphoric acid to lignin mass ratio of 2. Up to now, this is one of the highest values of apparent surface area reported not only for activated carbons prepared from lignin, but even for porous carbons prepared by chemical activation of other lignocellulosic materials with phosphoric acid. The use of lignin and phosphoric acid co-solution provided larger and more homogeneous effective interactions between the carbon precursor and the activating agent, by the formation of phosphate esters in the lignin matrix, which seems to be a key factor in the subsequent treatments: promoting crosslinking reactions in the carbonaceous matrix during the oxidative treatment in air at 200 ºC and enhancing the development of a wide porosity during the following activation thermal treatment.